Computational Study of the Fries Rearrangement Catalyzed by Acyltransferase from Pseudomonas protegens - Xiang Sheng; Wolfgang Kroutil; Fahmi Himo (ChemistryOpen, 2024)
Abstract The acyltransferase from Pseudomonas protegens (PpATase) catalyzes in nature the reversible transformation of monoacetylphloroglucinol to diacetylphloroglucinol and phloroglucinol. Interestingly, this enzyme has been shown to catalyze the promiscuous transformation of 3‐hydroxyphenyl acetate to 2′,4′‐dihydroxyacetophenone, representing a biological version of the Fries rearrangement. In the present study, we report a mechanistic investigation of this activity of PpATase using quantum chemical calculations. A detailed mechanism is proposed, and the energy profile for the reaction is presented. The calculations show that the acylation of the enzyme is highly exothermic, while the acetyl transfer back to the substrate is only slightly exothermic. The deprotonation of the C6−H of the substrate is rate‐limiting, and a remote aspartate residue (Asp137) is proposed to be the general base group in this step. Analysis of the binding energies of various acetyl acceptors shows that PpATase can promote both intramolecular and intermolecular Fries rearrangement towards diverse compounds.